The linkage between mental health, delinquency, and trajectories of delinquency: Results from the Boricua Youth Study. (May 2019) - Jennings, Wesley G.; Maldonado-Molina, Mildred; Fenimore, Danielle M.; Piquero, Alex R.; Bird, Hector; Canino, Glorisa
Abstract: Purpose: To examine the longitudinal relationship between depression, delinquency, and trajectories of delinquency among Hispanic children and adolescents. Methods: Propensity score matching is used to match depressed and non-depressed youth and a combination of group-based trajectory and multinomial logistic regression techniques are used. Results: After adjusting for pre-existing differences between depressed and non-depressed youth, the causal relationship between depression and delinquency and the association between depression and trajectories of delinquency appears to be largely spurious. However, the effect of depression on predicting a high rate and increasing trajectory of delinquency is robust. Conclusions: Depression and high-rate offending are linked in a sample of Hispanic children and adolescents. Highlights: Depression is linked to delinquency prior to matching. After matching, the depression and delinquency link seems spurious. Depression is linked to delinquency trajectories. After matching, depression still linked with high rate delinquency.